2010
DOI: 10.1017/s0022149x10000441
|View full text |Cite
|
Sign up to set email alerts
|

Gill ectoparasite assemblages of two non-native Cichla populations (Perciformes, Cichlidae) in Brazilian reservoirs

Abstract: The gills of 41 Cichla piquiti and 39 C. kelberi from Itaipu and Lajes reservoirs, respectively, Brazil, were examined to describe the ectoparasite assemblages of these two non-native peacock-bass populations. All ectoparasite species of the two studied hosts (C. piquiti and C. kelberi) were dominant, but Ascocotyle sp. (metacercariae) was the prevalent (58.53%) and most abundant helminth species in C. piquiti hosts, while Sciadicleithrum ergensi was the dominant species in C. kelberi hosts. Gill ectoparasites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
2
8
1
Order By: Relevance
“…The results described herein are in accordance with Kritsky et al (1989) and Yamada et al (2011), who found the monogenean G. tucunarense parasitizing gills of two species of cichlid, C. ocellaris and C. kelberi respectively, being common the setting of this kind of monogenoide parasite in this (Kritsky et al 1989). Indeed, several studies report the parasitism of G. disparoides in gills of H. severus, C. amazonarum and C. ocellaris and all these fish species are currently being raised in confined environments in the Peruvian Amazon.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…The results described herein are in accordance with Kritsky et al (1989) and Yamada et al (2011), who found the monogenean G. tucunarense parasitizing gills of two species of cichlid, C. ocellaris and C. kelberi respectively, being common the setting of this kind of monogenoide parasite in this (Kritsky et al 1989). Indeed, several studies report the parasitism of G. disparoides in gills of H. severus, C. amazonarum and C. ocellaris and all these fish species are currently being raised in confined environments in the Peruvian Amazon.…”
supporting
confidence: 81%
“…Several studies report the parasitism of neotropical cichlids by monogeneans belonging to Gussevia Kohn et Paperna, 1964(Kritsky et al 1989, Vidal-Martinez et al 2001, Yamada et al 2011, Mendoza-Franco et al 2010. For South America thirteen species of Gussevia have been described for eight species of cichlids (Kritsky et al 1986(Kritsky et al , 1989, evidencing a high specificity of Gussevia species parasitizing cichlids.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(metacercariae) in peacock basses collected in the Itaipú Reservoir, State of Paraná. Yamada et al (2011) inventoried the ectoparasites S. ergensi, Gussevia tucunarense Kritsky, Thatcher, and Boeger, 1986, G. undulata and Ascocotyle sp. of peacock basses collected in the Lajes Reservoir, State of Rio de Janeiro.…”
Section: Introductionmentioning
confidence: 99%